No evidence for persistent natural plague reservoirs in historical and modern Europe - Stenseth, Nils Chr; Tao, Yuxin; Zhang, Chutian; Bramanti, Barbara; Büntgen, Ulf; Cong, Xianbin; Cui, Yujun; Zhou, Hu; Dawson, Lorna A.; Mooney, Sacha J.; Li, Dong; Fell, Henry G.; et al. (Proceedings of the National Academy of Sciences - PNAS, 2022)
Caused by Yersinia pestis, plague ravaged the world through three known pandemics: the First or the Justinianic (6th–8th century); the Second (beginning with the Black Death during c.1338–1353 and lasting until the 19th century); and the Third (which became global in 1894). It is debatable whether Y. pestis persisted in European wildlife reservoirs or was repeatedly introduced from outside Europe (as covered by European Union and the British Isles). Here, we analyze environmental data (soil characteristics and climate) from active Chinese plague reservoirs to assess whether such environmental conditions in Europe had ever supported “natural plague reservoirs”. We have used new statistical methods which are validated through predicting the presence of modern plague reservoirs in the western United States. We find no support for persistent natural plague reservoirs in either historical or modern Europe. Two factors make Europe unfavorable for longterm plague reservoirs: 1) Soil texture and biochemistry and 2) low rodent diversity. By comparing rodent communities in Europe with those in China and the United States, we conclude that a lack of suitable host species might be the main reason for the absence of plague reservoirs in Europe today. These findings support the hypothesis that longterm plague reservoirs did not exist in Europe and therefore question the importance of wildlife rodent species as the primary plague hosts in Europe.